An updated checklist of the extant freshwater ostracods (Podocopida, Ostracoda, Crustacea) of Slovenia - Nataša Mori; Ali Šalamun (Natura Sloveniae)
The article presents an updated checklist of the extant freshwater ostracods in Slovenia. The data were obtained from the published scientific literature up to 2012 and from field collections after 2012, mainly from springs and groundwaters and, to a lesser extent, from ponds and other surface waters. The erroneous and invalid species names cited in the existing literature are listed to avoid further misquotations. The updated checklist contains a total of 70 valid species names. The species belong to 3 superfamilies, 9 families and 32 genera. The species-richest is the family Candonidae (36 species), followed by the family Cyprididae (22 species). Further field samplings are needed to complete the species list, with the focus on the eastern and southeastern parts of Slovenia, and on the sampling of surface waters. Additionally, more in-depth literature investigations and examinations of old museum collections across Europe need to be carried out to obtain all existing data. Moreover, many stygobiotic species (i.e., species inhabiting exclusively subterranean waters), new for science, collected over the last 20 years, need to be scientifically described. Lastly, the Slovenian National Red list on ostracods needs to be urgently updated.